Study guides

☆☆

Q: What is the answer to the equation x2 plus 6x plus 6 equals 0?

Write your answer...

Submit

Related questions

y = x2 - 6x + 2 y = x2 - 6x + 9 - 7 y = (x - 3)2 - 7

You don't have an equation there.

x2 + 6x = 16=> x2 + 6x - 16 = 0=> x2 + 8x -2x - 16 = 0=> (x+8)(x-2) = 0=> x = -8 or x = 2So, the solutions of the quadratic equation x2 + 6x = 16 are -8 and 2.

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

A quadratic equation. If you wish to solve for x, you can do so as follows: -x2 + 6x + 7 = 0 x2 - 6x - 7 = 0 (x - 7)(x + 1) = 0 x ∈ {-1, 7}

x = 2 and x = 4

hyperbola

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

Equals anything... x is a variable. If that equation was set equal to zero then you could solve for x, but that is not what you have asked.

x=1 and x=-7 are.

Line of symmetry: x = 3

x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

In the equation x2 = 6x - 9, all terms must be moved to one side of the equals sign, giving x2 - 6x + 9 = 0. This becomes factorable to (x -3)(x-3).

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

one

(3, -21)

Rearrange the quadratic equation to: x2-6x-9 = 0 and use the quadratic equation formula to find the values of x which are:- x = -1.2426406871 or x = 7.2426406871 When factored: (x+1.2426406871)(x-7.242406871) = 0

y â‰¥ 11

x^2+6x+2=9 x^2+6x-7=0 (x+7)(x-1)=0 x=-6,1 for your roots

x = sq root of 36x = 6x = -6

This is a quadratic equation question in finding the possible values of x x2 - 6x = - 8 x2 - 6x + 8 = 0 Factorise the expression in the equation: (x-2)(x-4) = 0 Therefore: x = 2 or x = 4

x2 + 6x - 2 = 0 x2 + 6x + 9 = 13 (x + 3)2 = 13 x + 3 = ± √13 x = -3 ± √13

The centre is (3,-1) and the radius is sqrt(10).

(x-5)(x+11)